Large hemopericardium and pericardial tamponade from presumed erosion of a Watchman 2.5 device 1-year postimplantation. Issue 6 (2nd November 2022) - Chawla, Raveen; Troester, Collin; Mixon, Timothy A.
Abstract: Percutaneous left atrial appendage closure has allowed patients with atrial fibrillation who are at high risk of bleeding to safely discontinue their anticoagulant therapy shortly after device implantation. The procedure, however, comes with a small risk of complications, including pericardial effusion and tamponade. The complications pertaining to pericardial effusion occur mainly perioperatively. We present an 82-year-old man with a 24 mm Watchman 2.5 device who developed hemopericardium resulting in tamponade and shock from presumed erosion of the device into the pericardium 1 year after implantation.